2018
DOI: 10.5194/amt-11-593-2018
|View full text |Cite
|
Sign up to set email alerts
|

All-sky photogrammetry techniques to georeference a cloud field

Abstract: Abstract. In this study, we present a novel method of identifying and geolocalizing cloud field elements from a portable all-sky camera stereo network based on the ground and oriented towards zenith. The methodology is mainly based on stereophotogrammetry which is a 3-D reconstruction technique based on triangulation from corresponding stereo pixels in rectified images. In cases where clouds are horizontally separated, identifying individual positions is performed with segmentation techniques based on hue filt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Due to the financial and technical constraints of low cost forecasting systems, a direct retrieval of cloud height and tracking information from the sky images itself is mandatory. Stereoscopic approaches with two ASIs are frequently described in the literature (Allmen et al 1996, Kassianov et al 2005, Seiz et al 2007, Nguyen et al 2014, Beekmans et al 2016and Crispel et al 2017. Cloud heights are determined by matching segmented clouds from images taken simultaneously by two ASIs.…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the financial and technical constraints of low cost forecasting systems, a direct retrieval of cloud height and tracking information from the sky images itself is mandatory. Stereoscopic approaches with two ASIs are frequently described in the literature (Allmen et al 1996, Kassianov et al 2005, Seiz et al 2007, Nguyen et al 2014, Beekmans et al 2016and Crispel et al 2017. Cloud heights are determined by matching segmented clouds from images taken simultaneously by two ASIs.…”
Section: State Of the Artmentioning
confidence: 99%
“…Most motion vector validation are done indirectly by comparing the achieved forecast score (Quesada-Ruiz et al 2014 andPeng et al 2015) or by comparing the previously forecasted cloud cover with the corresponding real cloud cover (Huang et al 2012, Chow et al 2015and Zaher et al 2017. Others estimate motion vector uncertainties (Crispel et al 2017 andSchmidt et al 2016).…”
Section: Cloud Motion Vector Validation Of the Three Systems Comparedmentioning
confidence: 99%
“…Ghonima et al (2012) and Shields et al (2013) give rich and interesting reviews of sky imager systems and their applications. Several algorithms have now been proposed that enable us to retrieve an estimation of cloud cover (e.g., Long and DeLuisi, 1998;Li et al, 2011;Ghonima et al, 2012;Martinis et al, 2013;Silva and Echer, 2013;Cazorla et al, 2015;Kim et al, 2016;Krinitskiy and Sinitsyn, 2016) or solar irradiance (Pfister et al, 2003;Chu et al, 2014;Chauvin et al, 2015;Kurtz and Kleissl, 2017), to classify the type of observed clouds (e.g., Heinle et al, 2010;Kazantzidis et al, 2012;Xia et al, 2015;Gan et al, 2017), or to track them (Peng et al, 2015;Cheng, 2017;Richardson et al, 2017). Sky imagers have also been specifically used for the detection of cirrus (Yang et al, 2012) or thin clouds (Li et al, 2012) and contrail studies (Schumann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ghonima et al (2012) and Shields et al (2013) give rich and interesting reviews of sky imager systems and their applications. Several algorithms have now been proposed that enable us to retrieve an estimation of cloud cover (e.g., Long and DeLuisi, 1998;Li et al, 2011;Ghonima et al, 2012;Martinis et al, 2013;Silva and Echer, 2013;Cazorla et al, 2015;Kim et al, 2016;Krinitskiy and Sinitsyn, 2016) or solar irradiance (Pfister et al, 2003;Chu et al, 2014;Chauvin et al, 2015;Kurtz and Kleissl, 2017), to classify the type of observed clouds (e.g., Heinle et al, 2010;Kazantzidis et al, 2012;Xia et al, 2015;Gan et al, 2017), or to track them (Peng et al, 2015;Cheng, 2017;Richardson et al, 2017). Sky imagers have also been specifically used for the detection of cirrus or thin clouds (Li et al, 2012) and contrail studies (Schumann et al, 2013).…”
mentioning
confidence: 99%